Reduced Glutathione suppresses Oxidative Stress in Nonalcoholic Fatty Liver Disease - Irie, Makoto (Euroasian J Hepatogastroenterol, 2016)
BACKGROUND AND AIMS: Insulin resistance and cytokine production are key mechanisms leading to fatty change in the liver and may produce nonalcoholic steatohepatitis (NASH). Oxidative stress may also contribute to clinical progression from simple fatty liver (FL) to NASH. A therapy for insulin resistance and antioxidant has been applied to treat NASH, yet these treatments are not fully established. In the present study, we have evaluated whether an antioxidant agent, glutathione, prevents the development of NASH from FL. MATERIALS AND METHODS: Five patients with FL and 10 with NASH were enrolled in the study. Three hundred milligrams per day of glutathione was given orally to patients with nonalcoholic fatty liver disease (NAFLD) every day, and an oxidative stress marker and biochemical tests were analyzed before treatment and 1 and 3 months after starting the treatment. We measured serum levels of 8-hydroxy-2-deoxyguanosine (8-OHdG) and gamma-glutamyltranspeptidase (GGT). Immunohistochemistry for glutathione was performed on formalin fixed liver specimens obtained from liver biopsies. RESULTS: Before treatment, the NASH group had higher serum 8-OHdG and lower serum glutathione levels than the FL group. Immunohistochemistry revealed that a strong expression of glutathione was observed in zone 3 in both NASH and FL before treatment. Serum levels of alanine transaminase and 8-OHdG were significantly decreased after treatment in the NASH group. Gamma-glutamyltranspeptidase was decreased after treatment, although the decrease was statistically not significant. DISCUSSION: The present pilot study demonstrated that antioxidant therapy with glutathione may reduce the pathological oxidative stress in the liver in NASH, preventing the progression from NAFLD to NASH. HOW TO CITE THIS ARTICLE: Irie M, Sohda T, Anan A, Fukunaga A, Takata K, Tanaka T, Yokoyama K, Morihara D, Takeyama Y, Shakado S, Sakisaka S. Reduced Glutathione suppresses Oxidative Stress in Nonalcoholic Fatty Liver Disease. Euroasian J Hepato-Gastroenterol 2016;6(1):13-18.